1980
DOI: 10.2136/sssaj1980.03615995004400030024x
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Evaluation of Four Phosphorus Soil Tests in Relation to Phosphate Buffering and Labile Phosphate in Soils

Abstract: Four soil P tests — Olsen, Colwell, Bray, and Mehlich — were evaluated in a greenhouse experiment in relation to plant uptake, relative yield, labile P, and buffer capacity on 30 soils varying in pH from 5.4 to 8.1. The Olsen and Colwell tests were most highly correlated with plant uptake, and the Olsen and Bray tests with relative yield. When the soils were stratified into weakly, moderately, and strongly buffered groups, it was found that extraction of labile P was depressed by increasing buffer capacity mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

1980
1980
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(41 citation statements)
references
References 0 publications
3
36
0
2
Order By: Relevance
“…It was also shown by Holford and Mattingly (1979) that the more sensitive a soil test is to buffer capacity, the better the correlation between the soil test values and phosphorus uptake by ryegrass. However, in a subsequent study, using white clover on a much more variable group of soils, Holford (1980) found that the relative efficacy of a soil test may be affected by its over-sensitivity as well as undersensitivity to buffering. A soil test which is over-sensitive will underestimate available phosphate on strongly buffered soils, while a soil test which is under-sensitive will overestimate it.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also shown by Holford and Mattingly (1979) that the more sensitive a soil test is to buffer capacity, the better the correlation between the soil test values and phosphorus uptake by ryegrass. However, in a subsequent study, using white clover on a much more variable group of soils, Holford (1980) found that the relative efficacy of a soil test may be affected by its over-sensitivity as well as undersensitivity to buffering. A soil test which is over-sensitive will underestimate available phosphate on strongly buffered soils, while a soil test which is under-sensitive will overestimate it.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown recently that the amounts of labile phosphate extracted by some soil tests tend to decrease with inoreasing buffer capacity of the soils (Holford and Mattingly 1979). Because the magnitude of this effect, and hence the relative sensitivity to buffer capacity, varies between soil tests, it is reasonable to suppose that buffer capacity is an important soil property influencing inter-relationships between soil tests, particularly those that extract phosphate only from the labile pool (Holford 1980). It was also shown by Holford and Mattingly (1979) that the more sensitive a soil test is to buffer capacity, the better the correlation between the soil test values and phosphorus uptake by ryegrass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some bicarbonate extract solutions were also analysed by inductively coupled plasma techniques (ICP) to determine total P in the extracts (P TB ; detection limit 1 mg/ kg; using a Thermo Jarrell Ash Iris/HR Duo). Bicarbonate-extractable P is related to the quantity of labile P (Dalal and Hallsworth 1977;Holford 1980), and was used in this study as an estimate of labile P. Particle size analysis of the soil samples was carried out using the pipette method described in Gee and Bauder (1986), including sample pre-treatment for removal of soluble salts and organic matter (where necessary).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Few currently available soil extractants are capable of multi-nutrient extraction without sacrificing accuracy for one compound or another [1]. Plant-available soil P has been difficult to accurately assess across the naturally occurring pH range of soils (calcareous to acid) with a single extractant because soil pH and P solubility are highly interrelated [2] [3] and soil pH has a strong influence on soil-solution chemistry [4].…”
Section: Introductionmentioning
confidence: 99%